2011
DOI: 10.1007/s00436-011-2735-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression analysis of Entamoeba invadens profilins in encystation and excystation

Abstract: Cell motility by actin cytoskeleton is essential for differentiation processes of excystation and encystation of Entamoeba. We recently studied an actin depolymerizing factor (ADF)/cofilin (Cfl) of Entamoeba invadens (Ei), and demonstrated its contribution to the encystation and excystation of E. invadens through actin cytoskeletal reorganization. Profilin is also an actin-binding protein but its function is different from that of Cfl in actin assembly. This study investigated E. invadens profilins in relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…However, other proteins that appeared to be important in E. invadens development were not detected in our study. For example, the E. histolytica homologue of one of the cysteine proteases EiCP-B9 [35] , or profilins (such as EiPFN1 and EiPFN4; [36] ) that are expressed in the cyst stage of E. invadens , were not detected in our proteome study. These discrepancies could be due to the fact that we were only able to identify a fraction of all cyst-specific proteins.…”
Section: Resultsmentioning
confidence: 80%
“…However, other proteins that appeared to be important in E. invadens development were not detected in our study. For example, the E. histolytica homologue of one of the cysteine proteases EiCP-B9 [35] , or profilins (such as EiPFN1 and EiPFN4; [36] ) that are expressed in the cyst stage of E. invadens , were not detected in our proteome study. These discrepancies could be due to the fact that we were only able to identify a fraction of all cyst-specific proteins.…”
Section: Resultsmentioning
confidence: 80%
“…The expression levels of profilin (an actin‐binding protein) (Makioka et al. ), actophorin (a depolymerization factor of actin) and generation factor (a polymerization factor of actin) (Bouyer et al. ) were reported to be regulated in the encystment process of A. castellanii or E. invadens .…”
Section: Discussionmentioning
confidence: 99%
“…lamblia (Castillo-Romero et al 2009). The expression levels of profilin (an actin-binding protein) (Makioka et al 2012), actophorin (a depolymerization factor of actin) and generation factor (a polymerization factor of actin) (Bouyer et al 2009) were reported to be regulated in the encystment process of A. castellanii or E. invadens. It has thus been suggested that actin is necessary for encystment and that it plays a role in the maintenance of the cells' shape.…”
Section: Discussionmentioning
confidence: 99%
“…Entamoeba histolytica encodes three profilins with their identity in the range of 22%‐32% only (Figure S1). 68 Further investigations may help us justify the presence of three profilins in amoeba.…”
Section: Resultsmentioning
confidence: 99%